2014
DOI: 10.1016/j.jtherbio.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of skin temperature measurement by telemetry thermistors and a thermal camera during exercise in the heat

Abstract: Abstract. New technologies afford convenient modalities for skin temperature (T SKIN ) measurement, notably involving wireless telemetry and non-contact infrared thermometry. The purpose of this study was to investigate the validity and reliability of skin temperature measurements using a telemetry thermistor system (TT) and thermal camera (TC) during exercise in a hot environment. Each system was compared against a certified thermocouple, measuring the surface temperature of a metal block in a thermostaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 26 publications
2
59
0
Order By: Relevance
“…The HAST 11 consisted of three, 30-minute periods of exercise at fixed Ḣprod intensities relative to body mass (3, 12 4.5 and 6 W.kg -1 ), within hot dry conditions (44.7 ± 1.8°C and 18.1 ± 4.7 % relative humidity). 13 Peak Tre (38.20 ± 0.36 vs 38.16 ± 0.42°C, p = 0.54), sweat setpoint (36.76 ± 0.34 and 36.79 ± 0.38°C, p 14 = 0.68) and sweat gain (0.37 ± 0.14 and 0.40 ± 0.18 g.sec -1 .°C -1 , p = 0.40) did not differ between 15 HASTs. Typical error of measurement (TEM), coefficient variation (CV) and intra-class coefficient of 16 correlation (ICC) were 0.19°C, 0.5% and 0.80 for peak Tre, 0.21°C, 0.6% and 0.65 for sweat setpoint 17 and 0.09 g.sec -1 .°C -1 , 28% and 0.68 for sweat gain, respectively.…”
Section: Introductionmentioning
confidence: 77%
“…The HAST 11 consisted of three, 30-minute periods of exercise at fixed Ḣprod intensities relative to body mass (3, 12 4.5 and 6 W.kg -1 ), within hot dry conditions (44.7 ± 1.8°C and 18.1 ± 4.7 % relative humidity). 13 Peak Tre (38.20 ± 0.36 vs 38.16 ± 0.42°C, p = 0.54), sweat setpoint (36.76 ± 0.34 and 36.79 ± 0.38°C, p 14 = 0.68) and sweat gain (0.37 ± 0.14 and 0.40 ± 0.18 g.sec -1 .°C -1 , p = 0.40) did not differ between 15 HASTs. Typical error of measurement (TEM), coefficient variation (CV) and intra-class coefficient of 16 correlation (ICC) were 0.19°C, 0.5% and 0.80 for peak Tre, 0.21°C, 0.6% and 0.65 for sweat setpoint 17 and 0.09 g.sec -1 .°C -1 , 28% and 0.68 for sweat gain, respectively.…”
Section: Introductionmentioning
confidence: 77%
“…Single-use rectal probes (Henleys Medical, UK, Meter logger Model 401, Yellow Springs Instruments, Missouri, USA) were inserted 10 cm beyond the anal sphincter for core temperature (T CORE ) measurement. Telemetry thermistors (U-Type connected to Gen II GD38 transmitter, Eltek, UK) were attached to the mid-belly of the pectoralis major, biceps brachii, rectus femoris and gastrocnemius for measurement of skin temperature (T SKIN ) with data transmitted wirelessly to a datalogger (RX250AL 1000 series Wireless Squirrel Logger, Eltek) as per James et al (2014). Heart rate was monitored continuously using a Polar 810i heart rate monitor (Kempele, Finland).…”
Section: Physiological Measuresmentioning
confidence: 99%
“…It was hypothesised that IP would ameliorate the decline in the lactate turnpoint and V* O 2max during endurance running in the heat, providing potential as a simple, acute ergogenic technique for use prior to competition. prior to each test, as is common in similar trials (James et al 2014;Hayes et al 2014). Finally, participants were asked to prepare for each trial as they would a competition.…”
mentioning
confidence: 99%
“…Different studies observed higher temperature values measured by thermal sensors than by IRT at rest and during running exercise, and lower temperatures values for thermocouples compared to thermography measurements after exercise (10,16,38). The authors suggested that the low agreement between methods could be mainly due to the fixation method of the thermal sensors on the skin and its effect on convective and evaporative heat loss in the region where the thermocouple was fixed.…”
Section: Introductionmentioning
confidence: 98%